Profile and management of patients with low back pain complaints in a Brazilian Emergency Department: a cross-sectional retrospective study - Larissa Faria Borges; Ligia Loiola Cisneros; Danielle Aquino Silva; Amabile Borges Dario; Manuela Ferreira; Paulo Henrique Ferreira (Hospital de Clínicas de Itajubá, 2020)
Objective: To describe the demographic profile and the management of patients with low back pain (LBP) complaints presenting to the Emergency Department (ED) of a Brazilian public hospital. Methods: Retrospective, cross-sectional study using a convenience sample of patients with LBP triaged at the studied ED through the Manchester Triage System along a year. Data were extracted from electronic medical records. LBP presentations were classified as non-traumatic, traumatic, and non-spinal related pain according to the signs and symptoms reported. Data included patients' demographic profile, pain severity and management (e.g., imaging exams, medication prescription and hospitalization). Results: Data from 2016 patients was analyzed. Most were middle-aged adults (mean age = 40.5years, SD 15.7), female (n = 1043, 51.7%) and presented moderate pain intensity (score range 4 to 7 on the Visual Analogue Scale, n=1,471; 74.1%). Non-traumatic pain (n = 1,016; 50.4%) was the main cause of care-seeking. A total of 36.9% (n = 743) underwent imaging exams and 42.2% (n = 850) received medication. Patients with non-spinal related pain were three times more likely to receive opioid medication (OR = 2.96; 95%CI 2.30 to 3.79). Conclusion: Non-traumatic LBP (i.e., no history of trauma or red flags) was the main cause of LBP care-seeking in a Brazilian ED. Most patients were treated conservatively and without hospitalization. Opioids prescription and imaging exams, although performed on a smaller scale, were still used for of the management of this type of LBP.